IMAGE-DISCURSIVE CONSTRUCTION OF BODY BEAUTY IN SOCIAL MEDIA: EFFECTS ON FOLLOWERS' BODY AND EATING PERCEPTIONS - Ana Flávia de Sousa Silva; Letícia dos Santos Neves; Camila Cremonezi Japur; Thaís Rodrigues Penaforte; Fernanda Rodrigues Penaforte (Universidade do Estado do Rio de Janeiro, 2018)
Contemporary representations of beauty patterns are limited to a lean and sculpted body. Such representations are mainly outspread by social media. Instagram, and its strong imaging profile, is widely used to share fitness images that depict ideal-body models. The current study followed the qualitative approach to assess comments about body-exposure pictures in an Instagram fitness profile. Twelve pictures published between January and December 2017 were selected for the study. Comments about the pictures were subjected to content analysis. Three categories of analysis emerged from them: "Marvelous, goddess, diva, inspiration" - exaltation to the lean body; "My dream is to have this body"- desire for bodily metamorphosis; and "A wrong choice ruins the whole body"- blame and distortions in food relations. There was close association among thinness, beauty and happiness as inspiration and desire sources. In light of the foregoing, one can assume the existing strong desire for bodily re-construction, which gets mixed with the sense of longing for the re-construction of one's identity. There is the illusion that the outspread image of an ideal-body model is available to all, as long as the individual works out hard, dedicates him/herself to it and has the strong will to reach such model. At the same time, this search for the ideal body raises feelings of sadness and frustration when this model is not reached. The desire for bodily remodeling echoes on eating habits, which become distorted and lead to guilt, regret and to the need of pleasure control. Such process can end up in dysfunctional eating behaviors. DOI: 10.12957/demetra.2018.33305